2010
DOI: 10.1111/j.1465-3362.2009.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time activities that predict initiation, progression and reduction of cannabis use: A prospective, population‐based panel survey

Abstract: The influence of persons the leisure time was spent with was of higher relevance to most phases of cannabis use than the type of leisure time activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
2
11
1
1
Order By: Relevance
“…This differs from increases in tobacco use during cannabis abstinence or reductions found in other studies (28,29). Those preliminary studies, however, relied on self-report, were retrospective, and the cannabis quit attempts were most likely unassisted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This differs from increases in tobacco use during cannabis abstinence or reductions found in other studies (28,29). Those preliminary studies, however, relied on self-report, were retrospective, and the cannabis quit attempts were most likely unassisted.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with those results, a recent review by Peters and colleagues (27) showed that use of tobacco and cannabis, compared to cannabis use alone, was associated with poorer cannabis cessation outcomes, as well as more psychosocial problems, and greater likelihood of a cannabis use disorder. Some preliminary evidence also suggests that tobacco may be substituted and may increase during cannabis reductions or abstinence (28,29). Another study did not find evidence of tobacco substitution, but found that tobacco use only decreased in participants with >50% reduction in cannabis use (30).…”
Section: Introductionmentioning
confidence: 99%
“…First, during reduction or abstinence from one substance, substitution/compensatory use of the other substance may occur. Data supporting substitution are mixed, with some studies supporting a substitution effect, demonstrated by an increase in tobacco use during cannabis abstinence/reduction (Allsop et al, 2014; Copersino et al, 2006; Levin et al, 2010; Schaub et al, 2010), while others have found no evidence of increases in tobacco use during cannabis cessation (McClure et al, 2014a; Peters and Hughes, 2010). Yet, others have found reductions in tobacco use among those who reduced their cannabis use by more than 50% (Gray et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating existing data is important to understand the extent to which cannabis use may hinder some individuals' ability to quit tobacco or vice versa [34,35]. Preliminary evidence indicates that tobacco may substitute for reduced cannabis consumption [36,37] and, in some cases, cessation from both cannabis and tobacco may produce more severe withdrawal than cessation from either alone [38]. Furthermore, prior literature with other drug users has suggested that use of two drugs may influence response to treatment [39][40][41][42][43][44], and thus may have important treatment outcome implications.…”
Section: Introductionmentioning
confidence: 99%